The impact of music education on children’s cognitive and socioemotional development: A quasi-experimental study in the Guri Program in Brazil - Graziela Bortz; Beatriz Ilari; Nayana Di Giuseppe Germano; Andrea Parolin Jackowski; Hugo Cogo-Moreira; Patrícia Silva Lúcio (PLoS ONE, 2025)
Background Transferability of music education to cognitive and social skills has recently been explored, but its causal effects remain debatable. Objectives To examine the impact of the Guri music education program on children’s cognitive and socioemotional skills in children from underserved communities in São Paulo, Brazil.